Influence of surface copper content on Stenotrophomonas maltophilia biofilm control using chlorine and mechanical stress - Gomes, I. B. (2020)
This work aimed to evaluate the action of materials with different copper content (0, 57, 96 and 100%) on biofilm formation and control by chlorination and mechanical stress. Stenotrophomonas maltophilia isolated from drinking water was used as a model microorganism and biofilms were developed in a rotating cylinder reactor using realism-based shear stress conditions. Biofilms were characterized phenotypically and exposed to three control strategies: 10mg l1 of free chlorine for 10min, an increased shear stress (a fluid velocity of 1.5m s1 for 30s), and a combination of both treatments. These shock treatments were not effective in biofilm control. The benefits from the use of copper surfaces was found essentially in reducing the numbers of non-damaged cells. Copper materials demonstrated better performance in biofilm prevention than chlorine. In general, copper alloys may have a positive public health impact by reducing the number of non-damaged cells in the water delivered after chlorine exposure.